A Documentation of Hepatitis Outbreak in Chittagong - Biswas, Rajat Sanker Roy; Hasan, Fahim Ul; Sultana, Aklima; Uddin, Md Kamal; Chowdhury, Debashis; Rosy, Serajun Noor; Mamun, Shaikh Md Hasan (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Introduction: Hepatitis E Virus (HEV) causes outbreaks of jaundice and it is associated with morbidity and higher maternal mortality. There is a recent outbreak of hepatitis in the Chittagong city and present study is aimed to observe the clinical and serological trends along with outcome of hepatitis cases visiting two tertiary care hospitals Chittagong, Bangladesh. Methods: It was an observational study done in two tertiary care hospital of Chittagong in a period of 3 months (May, June & July 2018) among 230 patients of hepatitis. After inclusion with written informed consent patients were introduced a questionnaire. Their demographic data, risk behaviors were noted, history related to hepatitis were recorded. Examination was done and evaluation regarding presence of hepatic encephalopathy at bed site was noted. Later serological findings were evaluated. After collection of all data it were compiled and analyzed by SPSS- 20. Results: Among 230 cases age group, gender and locality of the study patients were analyzed where younger age groups specially 21-30 years 114(49.6%) and 31-40 years 38(16.5%) were the most affected group. Gender distribution was found mostly same. Halishahar area which is located in western part of the Chittagong city was found mostly affected 196(85.2%). Use of water from WASA (Water and Sewerage Authority) supply was 168(73%) and deep tubewel water was 56(24.3%). Among them 80(34.8%) subjects do not boil water Anorexia (74.8%) nausea (77.4%) vomiting (83.5%) history of fever (89.6%) passage of dark color urine (99.1%) and weakness (97.4%) were some common presenting complaints. Family history of jaundice was found in 40.9% of cases. Among all 216(93.91%) had clinical jaundice, 91(39.56%) had right upper quadrant of the abdomen pain, 41(17.8%) had hepatomegally, 14(6.1%) had spleenomegally, 24(10.4%) had signs of hepatic failure and 34(14.8%) female were pregnant. Anti HEV was found positive in 164(71.3%) cases, 12(5.2%) were positive for anti HAV, 6(2.6%) were positive for HBsAg. None was found anti HCV positive. Among all 4(1.8%) cases died due to hepatic failure or multi-organ failure with AKI. All of them were pregnant. Two pregnant lady had missed abortion. Among all 11(4.7%) cases loosed follow and 213(92.60%) cases had uneventful recovery. Conclusion: This outbreak of HEV was of usual pattern of morbidity and mortality, and therefore points to water supply and sanitation issues. Chatt Maa Shi Hosp Med Coll J; Vol.17 (2); Jul 2018; Page 2-5